Tuning Rex rules HTLV-1 pathogenesis - Nakano, Kazumi; Watanabe, Toshiki (Frontiers in Immunology, 2022)
HTLV-1 is an oncovirus causing ATL and other inflammatory diseases such as HAM/TSP and HU in about 5% of infected individuals. It is also known that HTLV-1-infected cells maintain a disease-free, immortalized, latent state throughout the lifetimes of about 95% of infected individuals. We believe that the stable maintenance of disease-free infected cells in the carrier is an intrinsic characteristic of HTLV-1 that has been acquired during its evolution in the human life cycle. We speculate that the pathogenesis of the virus is ruled by the orchestrated functions of viral proteins. In particular, the regulation of Rex, the conductor of viral replication rate, is expected to be closely related to the viral program in the early active viral replication followed by the stable latency in HTLV-1 infected T cells. HTLV-1 and HIV-1 belong to the family Retroviridae and share the same tropism, e.g., human CD4+ T cells. These viruses show significant similarities in the viral genomic structure and the molecular mechanism of the replication cycle. However, HTLV-1 and HIV-1 infected T cells show different phenotypes, especially in the level of virion production. We speculate that how the activity of HTLV-1 Rex and its counterpart HIV-1 Rev are regulated may be closely related to the properties of respective infected T cells. In this review, we compare various pathological aspects of HTLV-1 and HIV-1. In particular, we investigated the presence or absence of a virally encoded “regulatory valve” for HTLV-1 Rex or HIV-1 Rev to explore its importance in the regulation of viral particle production in infected T cells. Finally, we reaffirm Rex as the key conductor for viral replication and viral pathogenesis based on our recent study on the novel functional aspects of Rex. Since the activity of Rex is closely related to the viral replication rate, we hypothesize that the “regulatory valve” on the Rex activity may have been selectively evolved to achieve the “scenario” with early viral particle production and the subsequent long, stable deep latency in HTLV-1 infected cells.